Advancing the New Afton Copper-Gold Project - Kevin Ross (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
Feasibility Study Team Processing / Engineering?Hatch, Vancouver Mining / Reserves?Australian Mine Consultants, Brisbane Geology / Resources?Roscoe Postle Associates, Vancouver Environmental / Permitting?Rescan, Vancouver Tailings BGC, Kamloops Probable Mine Components Mining tending towards caving methods Underground mine accessed by shaft /conveyor & decline Processing plant producing copper concentrate containing gold Concentrate trucked to rail head for export Non saturated tailings disposal